AGGRESSIVENESS IN CHILDREN OF KINDER AND ELEMENTARY SCHOOL OF METROPOLITAN AREA - Leiva Díaz, Viriam (2013)
In this descriptive investigation, including 154 children between 5 and 9 years old, in four different schools from the metropolitan area. Four variables were defined: socio demographic data, aggressive knowledge concepts, scholar and familial areas in relation with aggression. The results show that at levels, school and house, children perceive aggressive behaviors of different magnitude, and identify the role-played in the dynamics of aggression.